Explaining the involvement and investment of women in business angel groups: The impact of organizational context and investment experience - Cohen, Laurence; Bellavitis, Cristiano; Wirtz, Peter (Journal of Corporate Finance, 2025)
This research contributes to the scarce but growing literature on women angel investors. More specifically, leveraging stereotype threat theory, we investigate the role played by the social environment in shaping investing behavior across genders. This study offers a comparison between female angels from a stereotype-threat–free environment and (a) male angels, and (b) female angel investors investing in a strongly male-dominated environment. Using proprietary survey data of 96 business angels, our findings confirm that the social context plays an important role in explaining female investment behavior and involvement in BA-group activities. We find that women in a female-only group do not feature investment behavior that differs significantly from men. Whereas women who invest as a minority in a male-dominated environment tend to behave differently. Investment experience, however, moderates the influence of male-dominated environments on female investment behavior. The study confirms earlier exploratory findings related to the role of stereotype threat in female business angel activity at the individual level. Contributing to stereotype threat theory and gender studies in the business angel literature, our findings suggest that the historically marginal contribution of women is a result of the social construction of their role in the finance industry, in which stereotype threats may be particularly prevalent, rather than of supposedly innate features of gender.